Comparison of the Effects of Chamomile and Calendula Ointments on Diaper Rash - Zahra Afshari; Mahnaz Jabraeili; Maliheh Asaddollahi; Morteza Ghojazadeh; Yusuf Javadzadeh (Mashhad University of Medical Sciences, 2015)
Background: Diaper Rash is a common skin disorder in the infancy that makes infants and their parents anxious and nervous. Due to the high prevalence of dermatitis and its complications in addition to adverse effects of chemical drugs, herbal therapy is an appropriate solution. Aim: Comparison of the effects of Chamomile and Calendula ointments on severity of Diaper Rash. Methods: This double-blind randomized controlled trial was conducted on 90 infants under one year who were hospitalized in Sabalan Hospital of Ardebil. The infants were treated by Chamomile and Calendula ointments for one week. The severity of dermatitis was evaluated on days one, 3 and 7.  In order to assess the severity of dermatitis, the checklist of Diaper Rash five-point scale was used. Data were analyzed by software SPSS version 14 using chi-square, ANOVA, T-Test. Results: The age in the Chamomile group was (8. 8 ± 2.3) and in Calendula group was (9.0± 2.4) months. The severity of dermatitis in Chamomile group before treatment was 1.6 ± 0.5, on the third day 0.8 ± 0.4, and on the seventh day zero (p